Photo-damage, photo-protection and age-related macular degeneration - Marquioni Ramella, Melisa Daniela (2015)
Age-related macular degeneration (AMD) is a degenerative retinal disease that causes blindness in people 60-65 years and older, with the highest prevalence appearing in people 90 years-old or more. Epidemiological estimates indicate that the number of cases is increasing, and will almost double in the next 20 years. Preventive measures require precise etiological knowledge. This is quite difficult, since AMD is a multifactorial condition with intricate relationships between causes and risk factors. In this review, we describe the impact of light on the structure and physiology of the retina and the pigment epithelium, taking into account the continuous exposure to natural and artificial light sources along the life of an individual. A large body of experimental evidence demonstrates the toxic effects of some lighting conditions on the retina and the pigment epithelium, and consensus exists about the importance of photo-oxidation phenomena in the causality chain between light and retinal damage. Here, we analyzed the transmission of light to the retina, and compared the aging human macula in healthy and diseased retinas, as shown by histology and non-invasive imaging systems. Finally, we have compared the putative retinal photo-sensitive molecular structures that might be involved in the genesis of AMD. The relationship between these compounds and retinal damage supports the hypothesis of light as an important initiating cause of AMD.